Climate Change and Metal & Mining Sector: An Overview of Trends, Project Potential and its Abatement - P. K. N. Raghavan (The Minerals, Metals and Materials Society, 2011)
This paper identifies potential technologies for Carbon dioxide abatement from the mining and metal industry with special reference to the Aluminium industry. Mine reclamation could contribute to this effort to successfully reach the greenhouse gas (GHG) emissions reduction commitments for a nation. An overview of GHG production by the mining and metal industry together with a review of principles used to set the context in which specific options for GHG reduction are described. Options for GHG reduction in the mining and metal industry include reforestation, Addition of soil amendments or neutralizing agents, CO2 capture and storage, initiatives towards energy reduction, waste heat recovery and alternative energy use. An analysis and quantification of the potential GHG reduction of potential carbon sinks and sequestration options for the mining and metal industry are provided. Cost estimates for different options are provided. The paper also identifies sources that could fund research regarding GHG reduction options. The paper concludes with recommendations.